Bacillus thuringiensis CHGP12 uses a multifaceted approach for the suppression of Fusarium oxysporum f. sp. ciceris and to enhance the biomass of chickpea plants. Issue 1 (8th October 2022) - Fatima, Rida; Mahmood, Tahir; Moosa, Anam; Aslam, Muhammad Naveed; Shakeel, Muhammad Taimoor; Maqsood, Ambreen; Shafiq, Muhammad Umar; Ahmad, Tanvir; Moustafa, Mahmoud; Al‐Shehri, Mohammad
Abstract: BACKGROUND: Bacillus species synthesize antifungal lipopeptides (LPs) making them a sustainable and eco‐friendly management option to combat Fusarium wilt of chickpea. RESULTS: In this study, 18 endophytic Bacillus strains were assessed for their antifungal activity against Fusarium oxysporum f. sp. ciceris (FOC) associated with Fusarium wilt of chickpea. Among them, 13 strains produced significant inhibition zones in a direct antifungal assay while five strains failed to produce the inhibition of FOC. Bacillus thuringiensis CHGP12 exhibited the highest inhibition 3.45 cm of FOC. The LPs extracted from CHGP12 showed significant inhibition of the pathogen. Liquid chromatography–mass spectrometry (LC–MS) analysis confirmed that CHGP12 possessed the ability to produce fengycin, surfactin, iturin, bacillaene, bacillibactin, plantazolicin, and bacilysin. In an in vitro qualitative assay CHGP12 exhibited the ability to produce lipase, amylase, cellulase, protease, siderophores, and indole 3‐acetic acid (IAA). IAA and gibberellic acid (GA) were quantified using ultra‐performance liquid chromatography (UPLC) with 370 and 770 ng mL −1 concentrations of IAA and GA respectively. Furthermore, the disease severity showed a 40% decrease over control in CHGP12 treated plants compared to the control in a glasshouse experiment. Moreover, CHGP12 also exhibited a significant increase in total biomass of the plants namely, root and shoot growth parameters, stomatal conductance, and photosynthesis rate. CONCLUSION: In conclusion, our findings suggest that B. thuringiensis CHGP12 is a promising strain with high antagonistic and growth‐promoting potential against Fusarium wilt of chickpea. © 2022 Society of Chemical Industry. Abstract : Bacillus thuringiensis CHGP12 showed promising antifungal activity against Fusarium oxysporum f. sp. ciceris . The antifungal activity of CHGP12 was due to lipopeptides detected through liquid chromatography–mass spectrometry (LC–MS). CHGP12 showed protease, lipase, cellulase, amylase, siderophores, indole 3‐acetic acid (IAA) and gibberellic acid (GA) producing ability. CHGP12 suppressed the Fusarium wilt disease and promoted the growth of chickpea plants.